PENGARUH IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT. KARIMUN SEMBAWANG SHIPYARD - Cesilia Rahael Ardi Hapsari; Seno Andri; Syofiatul Safitri (Bisnis-Net, 2023)
Indonesia as a maritime country certainly has a greater opportunity to develop the country's economy in the maritime industry sector, one of which is the shipping industry, this study aims to analyze the influence of organizational climate on employee performance through work motivation as an intervening variable, The research method used is quantitative methods with primary and secondary data sources. Data collection using questionnaires distributed to respondents, The sample in this study amounted to 70 respondents of PT. Karimun Sembawang Shipyard with sampling techniques, namely non probability sampling or total sampling. Data analysis includes Outer Model, Inner Model and Hypothesis Test using SmartPLS 4. The results showed, (1) there is a significant influence of organizational climate on the performance of PT. Karimun Sembawang Shipyard, (2) there is a significant influence of organizational climate on the work motivation of PT. Karimun Sembawang Shipyard, (3) there is a significant influence of work motivation on the performance of PT. Karimun Sembawang Shipyard, (4) there is an influence that the organizational climate on performance through the work motivation of PT. Karimun Sembawang Shipyard.Keywords: Organizational Climate, Employee Performance, Work Motivation